Analisis dan Evaluasi Kamera Thermal Untuk Pengukuran Suhu Badan - Satriyo Satriyo (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2021)
The use of thermal cameras is currently very widespread in both the industrial and health world. Application in the health sector, especially for measuring the patient's body temperature, certainly requires a good level of accuracy so that the patient's temperature reading results are reliable. In this study, two types of thermal cameras were evaluated, namely the MLX 90640 and AMG8833. The MLX 90640 thermal camera is connected to a raspberry pi and the scanned image is displayed on the monitor screen. The two thermal cameras were evaluated in terms of the accuracy of temperature readings and the resolution of the images. The test results of the two thermal cameras, the average accuracy of MLX90640 = 3,7% while for AMG8833 = 21,9%. In terms of image resolution, the MLX90640 temperature scan is better than the AMG8833.